Phase Behaviours of Polymeric Blends Containing Block Copolymers - Xie, Jiayu (My University, 2023)
Blending different polymers together provides a simple yet effective method for producing unconventional structured materials. However, understanding the interplay between macro- and microphase separations poses a challenge when studying the phase behaviours of polymeric blends containing block copolymers. In this thesis, we advance our knowledge of polymeric blend self-assembly by investigating several informative blending systems using self-consistent field theory (SCFT). We begin with straightforward blending formulations, such as binary A1B1/A2 and A1B1/A2B2 blends, to conduct systematic investigations into their phase behaviours. Our focus is on the formation and stability of recently discovered Frank-Kasper (FK) phases. The unveiled correlation between the various system parameters, the behaviours of various polymeric components, and the stability of the FK phases deepens our understanding of the emergence of these unconventional spherical phases in polymeric mixtures composed of simple components. Expanding our study, we investigate more general AB/C binary blends and AB/C/D ternary blends, resembling surfactant/water and surfactant/water/oil systems. In agreement with recent experiments, we find that the addition of corona-selective C homopolymers into diblock copolymers reduces the critical conformational asymmetry of the diblocks required to stabilize the FK σ phase. Furthermore, the simultaneous presence of core- and corona-selective components greatly enhances the stability of the FK phases, particularly the Laves phases. Our results provide insights into the formation of FK phases in a broader range of soft matter systems containing amphiphilic molecules and selective additives. Next, in seeking alternatives to architecturally complex block copolymers for fabricating binary crystalline phases, we turn our attention to AB/CD binary blends. With designed secondary interactions, we demonstrate that this system can stabilize various binary crystals with varying stoichiometries. Our analysis of chain packing within various phases sheds light on the mechanisms governing the selection of the equilibrium crystal in this system. Lastly, we explore the topological effects of copolymers in their blends with homopolymers. Although the topological nonequivalency between ABA and BAB linear triblock copolymers results in only slight differences in their equilibrium phase behaviours, these differences are dramatically magnified when blended with A homopolymers. Compared to ABA/A blends, BAB/A blends exhibit much poorer miscibility, and the Lifshitz points of these two polymeric blends are qualitatively different. The results presented in this thesis enhance our understanding of the equilibrium phase behaviours of polymeric blends containing block copolymers, including blend miscibility and structural formation, thus laying a solid foundation for future research into more complex blending systems.